Pengaruh Kepemimpinan Transformasional dan Terdistribusi Kepala Sekolah Dasar terhadap Prestasi Akademik dan Nonakademik Peserta Didik - Usman Usman (Lembaga Yasin AlSys, 2026)
Although elementary school principals’ leadership practices have been widely examined, studies that simultaneously test the effects of transformational and distributed leadership on students’ academic and non-academic achievement in the Indonesian context, particularly in Barru Regency, remain limited. This study aimed to analyze the influence of principals’ transformational and distributed leadership on the academic and non-academic achievement of elementary school students in Barru Regency. The research was conducted from October to November 2025 using a quantitative approach with an explanatory survey design, involving 210 teachers from 15 public elementary schools selected through proportional random sampling. Data were collected using standardized questionnaires and documentation of students’ academic scores and non-academic achievements, and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The measurement model results showed that all indicators met the validity and reliability criteria (outer loading > 0.70; AVE > 0.50; CR > 0.70). The structural model yielded R² values of 0.64 for academic achievement and 0.58 for non-academic achievement. Hypothesis testing indicated that transformational leadership had a significant effect on academic achievement (β = 0.45; p < 0.001) and non-academic achievement (β = 0.32; p < 0.001), while distributed leadership also had a significant effect on academic achievement (β = 0.29; p < 0.001) and non-academic achievement (β = 0.41; p < 0.001). These findings contribute to the development of educational leadership theory by integrating visionary transformational leadership and collaborative distributed leadership in the comprehensive enhancement of learning outcomes. The study concludes that the synergy of these two leadership approaches plays an important role in improving students’ academic and non-academic achievement and recommends strengthening principal leadership development programs in Barru Regency.